How Aflac used advertising to increase the value of its corporate brand - Gregory, James R. (Henry Stewart Talks, 2017)
The case study reviews how Aflac, a US insurance company, increased the value of their brand by embarking on a comprehensive advertising campaign that exploited the similarity between the company’s name and a duck’s quack.